Pengaruh Peran Aktivitas Bermain Buku Cerita Bergambar dalam Pengembangan Keterampilan Bahasa Anak Usia Dini - Tina Magfiroh Inzany; Syamsiah Depalina Siregar (PT. Willy Print Art, 2025)
This study aims to examine the influence of play-based activities using picture storybooks on the development of language skills in early childhood at TK Dharma Wanita, Kotanopan, Kotanopan District. Language skills are a crucial aspect of early childhood development, directly linked to communication abilities, message comprehension, and verbal or non-verbal expression. Playing with picture storybooks is a fun and effective approach to stimulate children's language abilities by combining visual elements, imagination, and verbal interaction. This research employed a quantitative method using a quasi-experimental design, involving an experimental group and a control group. The findings reveal that children engaged in picture storybook play activities showed a significant improvement in speaking, listening, vocabulary, and story comprehension compared to those who did not receive the same treatment. These results suggest that integrating picture storybooks into play activities is an effective strategy for enhancing early childhood language skills